Wasted Bread as Substrate for the Cultivation of Starters for the Food Industry - Verni, Michela; Minisci, Andrea; Convertino, Sonia; Nionelli, Luana; Rizzello, Carlo G. (Frontiers in Microbiology, 2020)
The amount of bread wasted daily worldwide, throughout its entire lifecycle, from production to distribution, is estimated to be hundreds of tons, therefore representing both economic and environmental issues. This work aimed at the valorization of wasted bread, setting-up a protocol for obtaining a growth medium to be used for the cultivation of food industry microbial starters. The optimization of the protocol included the set-up of parameters for the hydrolysis of the bread nutrient compounds with proteolytic and amylolytic enzymes and the supplementation with nitrogen and/or carbon sources. The suitability of the optimized medium for the growth of lactic acid bacteria, yeasts and fungi from dairy, bakery, and wine industries was assessed. Lactic acid bacteria growth was strongly affected by the quantity and quality of nitrogen sources employed, while yeasts and fungi growth exceeded that obtained with the reference media commonly employed for their cultivation. Wasted Bread Medium (WBM) represents a realistic option for the valorization and re-use of bread waste, responding to the modern vision of circular economy.